Telescoping of isotherms beneath the South Tibetan Detachment, Mount Everest Massif: implications for magnitude of internal flow during extrusi on of the Greater Himalayan Slab - Law, Richard D; Jessup, Micah J; Searle, Michael P; Cottle, John M; Waters, David (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1281 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.86-87